We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
39
1
avatar

Find \(3 + \frac{1}{3 + \frac{1}{3 + \frac{1}{3 + \frac{1}{3 + ...}}}}\)

 Oct 28, 2019
 #1
avatar+104932 
+1

Let the given expression  = x

 

So....we have that

 

x  =  3  +   1 / x

 

x - 3  =  1  / x              multiply through by  x

 

x^2  - 3x   =  1             complete the square on x

 

x^2 - 3x + 9/ 4  =  1 + 9/4

 

(x - 3/2)^2  =  13/4       take the positive root

 

x - 3/2  = √13 / 2

 

x =  [ 3  + √13 ]

      __________

              2

 

 

cool cool cool

 Oct 28, 2019
edited by CPhill  Oct 28, 2019

19 Online Users

avatar
avatar